2018
DOI: 10.1002/chem.201800194
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochromic Polymers That Turn Green Upon the Dissociation of Diarylbibenzothiophenonyl: The Missing Piece toward Rainbow Mechanochromism

Abstract: Mechanochromic polymers, that is, polymers sensitive to mechanical impact, promise great potential for applications in damage sensors. In particular, radical-type mechanochromic polymers, which produce colored radical species in response to mechanical stress, may enable not only the visualization of mechanical stress, but also its quantitative evaluation by electron paramagnetic resonance analysis. Herein, a radical-type mechanochromic polymer that exhibits a color change from white to green upon dissociation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 35 publications
1
74
0
2
Order By: Relevance
“…Combinations of these mechanophores can be used in tandem to produce a wide range of colors. 60 This has recently led to the exciting report of mechanochromic polymer blends that can recognize different mechanical stimuli. 61 These blends were composed of tetraarylsuccinonitrile (TASN) (pink radical; Figure 18B) incorporated into the center of PS (''hard'' regions) and diarylbibenzothiophenonyl (DABBT) (green radical; Figure 18C) incorporated into the center of a star-shaped polystyrene-b-poly(methyl acrylate) (''soft'' regions).…”
Section: Compressionmentioning
confidence: 99%
“…Combinations of these mechanophores can be used in tandem to produce a wide range of colors. 60 This has recently led to the exciting report of mechanochromic polymer blends that can recognize different mechanical stimuli. 61 These blends were composed of tetraarylsuccinonitrile (TASN) (pink radical; Figure 18B) incorporated into the center of PS (''hard'' regions) and diarylbibenzothiophenonyl (DABBT) (green radical; Figure 18C) incorporated into the center of a star-shaped polystyrene-b-poly(methyl acrylate) (''soft'' regions).…”
Section: Compressionmentioning
confidence: 99%
“…Subsequent research demonstrated that mechanochemical activation of DABBF could be achieved in elastomeric linear polyurethanes under uniaxial tension for colorimetric stress sensing. 32 The same group has also identified tetraarylsuccinonitrile (TASN) 33 and diarylbibenzothiophenone (DABBT) 34 as mechanophores capable of producing pink-and green-colored radical fragments, respectively. The intrinsic thermal instability of these radical-type dynamic covalent molecules, however, limits their R. W. Barber et al…”
Section: Mechanochromic Reactions For Stress Sensingmentioning
confidence: 99%
“…[4][5][6][7][8] Die kontinuierliche Entwicklung neuer Mechanophore und ihrer jeweiligen Nachweismethoden ist jedoch von grçßter Bedeutung,u md ie kraftinduzierten molekularen Veränderungen und ihren Beitrag zum makroskopischen Versagen des Materials mit der von außen einwirkenden Kraft qualitativ und schließlich auch quantitativ zu korrelieren. Beliebte molekulare Strukturen sind u. a. Spiropyran [9][10][11][12] und seine Rhodamin Derivate, [13][14][15] Diels-Alder-Addukte mit latenten Anthracenen, [16][17][18][19][20][21] persistente delokalisierte Radikale, [22][23][24][25][26] und aggregachrome Farbstoffe. [27][28][29] Unter diesen kçnnen Fluorophore,d ie mit mechanischer Kraft "angeschaltet" werden, als die empfindlichsten angesehen werden.…”
Section: Die Optische Erkennung Von Schäden Und Drohendemunclassified
“…[1][2][3] Bis heute wurden eine Vielzahl von Mechanochromophoren und Mechanofluorophoren entwickelt, die bei mechanischer Belastung entweder ihre Absorptions-oder Emissionseigenschaften ändern und als empfindliche Kraftsonden im molekularen Maßstab dienen. Beliebte molekulare Strukturen sind u. a. Spiropyran [9][10][11][12] und seine Rhodamin Derivate, [13][14][15] Diels-Alder-Addukte mit latenten Anthracenen, [16][17][18][19][20][21] persistente delokalisierte Radikale, [22][23][24][25][26] und aggregachrome Farbstoffe. Beliebte molekulare Strukturen sind u. a. Spiropyran [9][10][11][12] und seine Rhodamin Derivate, [13][14][15] Diels-Alder-Addukte mit latenten Anthracenen, [16][17][18][19][20][21] persistente delokalisierte Radikale, [22][23][24][25][26] und aggregachrome Farbstoffe.…”
unclassified